European citizenship after Martínez Sala and Baumbast. Has European law become more human but less social? - Menéndez, Agustín José (Oslo, 2009)
"Martínez Sala and Bambaust have become the leading cases on free movement of persons in Community law. It has become standard to see both rulings as heralding a ‘civic’ turn of European integration, by expanding the personal scope of the freedom of personal movement from workers to citizens, and thus redefining the value basis of the law of the European Union. This would prove again the emancipatory potential of Community law, closely related to its redrawing the economic and political boundaries of Europe, and getting rid of discriminatory obstacles in the way of citizens’ freedom. This paper contests this interpretation. It shows why Martínez Sala and Baumbast are not epochal judgments, but logical extensions of the pre-Maastricht case of the Court. Furthermore, it reveals why and how Martínez Sala and Baumbast have radicalised the processes of Europeanisation of what used to be exclusive national competences, and the judicialisation of decision-making processes where representative institutions used to have the exclusive word. This has rather negative consequences, both in terms of the democratic legitimacy of the Union and the distributive consequences of Community law. European law may have become more humane only at the expense of its being less social, to the extent it imports a non-solidaristic logic into provinces of the legal system before sheltered from economic pressure, and may end up forcing a social retrenchment. The market citizen has not been overcome, but has only been dressed in political clothes."